Ecofisiologia de feijão-caupi submetido a deficiência hídrica nos sistemas de plantio direto e convencional - Freitas, Rômulo Magno Oliveira de (Universidade Federal Rural do Semi-Árido, 2015)
The cowpea crop has great importance for the Brazilian Northeast, especially for the poorest population. One of the major problems encountered for this crop is drought stress caused by erratic rainfall, coupled with the high temperatures common in this region. The no-tillage system has features, such as reduction of soil water evaporation, higher water retention and lower soil temperature fluctuations, and can be a way to minimize the water stress in a cowpea crop. Two experiments were carried out at the experimental garden in the Departamento de Ciências Vegetais of the Universidade Federal Rural do Semi-Árido (UFERSA), in Mossoró city, RN, with the aim of evaluating the use and use efficiency of water, and the ecophysiological traits of cowpea plants under water shortage in tillage and no-till cropping systems. The first experiment was conducted in a randomized complete blocks design with subsampling and four replications. The treatments were the two cropping systems (tillage and no-till), and the subsamples were the six periods of irrigation suspension (2; 6; 10; 14; 18 e 22 days), applied at the beginning of the flowering stage. The plants parts dry mass and the leaf area 64 days after sowing (DAS), and the grain production, water use and water use efficiency at that 70 DAS were evaluated. For the second experiment, it was used a randomized complete blocks design with subsampling and sub-subsampling, with four replications. The treatments were the cropping systems (tillage and no-till), and the subsamples were three water availability conditions (no shortage, moderate shortage and severe shortage), and the sub-subsampling were the evaluation periods. Plants dry mass, leaf areas, photosynthesis, stomatal conductance, transpiration, lowest leaf CO2 internal concentration and leaf water potential were evaluated. In the first experiment, it was observed that the no-till system is promising for the cowpea crop, with better grain production and better water use efficiency. In this system, the cowpea cultivation was possible even under a moderate water shortage. Prolonged water shortage periods did affect the dry mass accumulation, grain yield and water use efficiency. In the second experiment, the water shortage affected all the studied variables, with the exception of the leaves water potential. The cowpea fully recovered all physiological traits after moderate and severe water shortage. Stomatal closure was the main mechanism of resistance to water shortage, and the cowpea may be considered as a water-saving species. The cropping system did not affect the photosynthesis rates. The plants had more dry weight and leaf areas at the no-till system
Cowpea ecophysiology subjected to water stress in no-tillage and conventional
Keywords: Vigna unguiculata; Ecophysiology - cowpea; Plantation system - water stress; Photosynthesis; Stomatal conductance - resistance to drough; Vigna unguiculata; Ecofisiologia feijão-caupi; Sistema de plantio deficiência hídrica; Fotossíntese; Condutância estomática - resistência à seca; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA